2019
DOI: 10.21834/e-bpj.v4i11.1726
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors and Attitude towards Safe Driving Scale among Young Adults in Malaysia

Abstract: The human factor is one of the major causes that contributed to a road traffic accident (RTA). This study aims to identify the correlation between sleep duration and safe driving attitude among young adult in Malaysia. The significant relationship showed between Domain (D) 1, 4 and 5 of ASDS-46 with sleep duration (ESS). D1 (self-complaint), D4 (self-concern) has positive correlation (p= .110 and .147) and D5 (driving style) has negative correlation (p=.132). In conclusion, short sleep duration may influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…To reiterate Safarpour et al (2020), the systematic approach to road safety will result in safer and courteous driving. Though human factors are to be blamed for road mishaps (Masuri, Asib, Dahlan, & Isa, 2019), curtailing the attitudes through proper road education is recommended. Also, further studies on this issue are suggested by undertaking a quantitative method.…”
Section: Discussionmentioning
confidence: 99%
“…To reiterate Safarpour et al (2020), the systematic approach to road safety will result in safer and courteous driving. Though human factors are to be blamed for road mishaps (Masuri, Asib, Dahlan, & Isa, 2019), curtailing the attitudes through proper road education is recommended. Also, further studies on this issue are suggested by undertaking a quantitative method.…”
Section: Discussionmentioning
confidence: 99%